Relationship of microRNA locus with type 2 diabetes mellitus: a case–control study. Issue 11 (3rd November 2021) - Huang, Qiuyu; Chen, Hanshen; Xu, Fan; Liu, Chao; Wang, Yafeng; Tang, Weifeng; Chen, Liangwan
Abstract : Type 2 diabetes mellitus (T2DM) is considered as a metabolic disease with hyperglycemia. Accumulating investigations have explored the important role of hereditary factors for T2DM occurrence. Some functional microRNA (miR) polymorphisms may affect their interactions with target mRNAs and result in an aberrant expression. Thus, miR variants might be considered as a biomarker of the susceptibility of T2DM. In this study, we recruited 502 T2DM cases and 782 healthy subjects. We selected miR-146a rs2910164 C>G, miR-196a2 rs11614913 T>C and miR-499 rs3746444 A>G loci and carried out an investigation to identify whether these miR loci could influence T2DM occurrence. In this investigation, a Bonferroni correction was harnessed. After adjustment, we found that rs2910164 SNP was a protective factor for T2DM (GG vs CC/CG: adjusted P  = 0.010), especially in never drinking (GG vs CC/CG: adjusted P  = 0.001) and BMI ≥24 kg/m 2 (GG vs CC/CG: adjusted P  = 0.002) subgroups. We also identified that rs11614913 SNP was a protective factor for T2DM in smoking subjects (CC/TC vs TT: adjusted P  = 0.002). When we analyzed an interaction of SNP–SNP with the susceptibility tof T2DM, rs11614913/rs3746444, rs2910164/rs3746444 and rs11614913/rs2910164 combinations were not associated with the risk of T2DM. In summary, this study highlights that rs2910164 SNP decreases the susceptibility of T2DM, especially in BMI ≥24 kg/m 2 and never drinking subgroups. In addition, we also identify that rs11614913 C allele decreases the susceptibility of T2DM significantly in smoking subgroup.